MERANCANG MANAJEMEN AGRIBISNIS SYARIAH DI DESA GUNUNG SARI, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Susi Melinasari; Hasbi Ash Shiddieqy; Siti Jaojah (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
This community service aims to Design a Sharia Agribusiness Management in Gunung Sari Village, Pamijahan District, Bogor Regency. This community service uses the method of discussions and participation. The agribusiness system includes the provision of production facilities, agro-industry/product processing systems, support systems, development of the agribusiness sector, development of agribusiness infrastructure, and guidance and empowerment as an effort to overcome the food crisis.